Daile' : Staatliches Tanzensemble der Lettischen SSR - Kakevsky, M; Shapov, V
Blue Latvian skyline (probably Riga); colourful couple wearing traditional clothes; black background Poster advertising the Latvian philharmonic ensemble 'Daile' PO-0287